Bispectral index monitoring as an adjunct to nurse-administered combined sedation during endoscopic retrograde cholangiopancreatography - Jang, Se Young (Baishideng Publishing Group Co., Limited, 2012)
AIM: To determine whether bispectral index (BIS) monitoring is useful for propofol administration for deep sedation during endoscopic retrograde cholangiopancreatography (ERCP). METHODS: Fifty-nine consecutive patients with a variety of reasons for ERCP who underwent the procedure at least twice between 1 July 2010 and 30 November 2010. This was a randomized cross-over study, in which each patient underwent ERCP twice, once with BIS monitoring and once with control monitoring. Whether BIS monitoring was done during the first or second ERCP procedure was random. Patients were intermittently administered a mixed regimen including midazolam, pethidine, and propofol by trained nurses. The nurse used a routine practice to monitor sedation using the Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale or the BIS monitoring. The total amount of midazolam and propofol used and serious side effects were compared between the BIS and control groups. RESULTS: The mean total propofol dose administered was 53.1 ± 32.2 mg in the BIS group and 54.9 ± 30.8 mg in the control group (P = 0.673). The individual propofol dose received per minute during the ERCP procedure was 2.90 ± 1.83 mg/min in the BIS group and 3.44 ± 2.04 mg in the control group (P = 0.103). The median value of the MOAA/S score during the maintenance phase of sedation was comparable for the two groups. The mean BIS values throughout the procedure (from insertion to removal of the endoscope) were 76.5 ± 8.7 for all 59 patients in using the BIS monitor. No significant differences in the frequency of < 80% oxygen saturation, hypotension (< 80 mmHg), or bradycardia (< 50 beats/min) were observed between the two study groups. Four cases of poor cooperation occurred, in which the procedure should be stopped to add the propofol dose. After adding the propofol, the procedure could be conducted successfully (one case in the BIS group, three cases in the control group). The endoscopist rated patient sedation as excellent for all patients in both groups. All patients in both groups rated their level of satisfaction as high (no discomfort). During the post-procedural follow-up in the recovery area, no cases of clinically significant hypoxic episodes were recorded in either group. No other postoperative side effects related to sedation were observed in either group. CONCLUSION: BIS monitoring trend to slighlty reduce the mean propofol dose. Nurse-administered propofol sedation under the supervision of a gastroenterologist may be considered an alternative under anesthesiologist.